Evaluation of the genotoxicity of diazinon on the mitotic Index and mitosis stages in the roots tips in Allium Cepa. L. (Sebha University Conference Proceedings, 2024)
This study aims to determine the genotoxicity of diazinon pesticide on the stages of mitosis in the growing tips of onion roots, Allium cepa. Three concentrations were used in this study: 20, 50, and 90 ppm, for a period of 12 and 24 hours. When the results were analyzed statistically, the results showed that diazinon has toxic effects, as it caused a decrease in the mitotic Index in the cells of the growing tips of onion plants. It was also found that diazinon has an effect on the stages of mitosis, where It led to an increase in the percentage of chromosomal abnormalities in the different stages of division, and thus a variety of imbalances in each stage of division. The most important of these imbalances were the granular primer, irregular, sticky, and the equatorial clumped one, C.metaphase, with bridges, and lagging chromosomes.